Pengaruh Perspektif Agama dan Suku Bagi Pemberdayaan Toleransi Mahasiswa Kristen Papua di Politeknik Amamapare Timika - Jimmy Rungkat; Theresia Yunie Puspita (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The purpose of this article is to reveal a more comprehensive dimension of tolerance among Papuan Christian students at Amamapare Polytechnic in Timika, especially through the lens of religious and ethnic perspectives. A qualitative method with descriptive analysis is applied in this study. The result of this study highlights that, from a religious perspective, students are generally more open in practicing religious tolerance on campus. This act is influenced by Christian teachings that students received through Religious Studies classes, church sermons, and parental guidance. From the ethnicity standpoint, students tend to act with lower level of interethnic tolerance. Even though, they can build friendships with peers from different ethnic groups, they are more loyal to friends with the same ethnicity. As Indigenous Papuans students, some of them also feel uncomfortable and perceive inequity particularly regarding the lack of support from government and customary institutions in safeguarding equal access to educational scholarships. Furthermore, the local wisdom in Mimika Regency that concern about the strengthening of tolerance still not be able to significantly influence students’ attitudes. The result of this study suggests that efforts to enhance tolerance among Papuan Christian students should focus more on interethnic rather than interreligious tolerance, alongside with promoting student dialogue that fosters understanding of other religions’ practices and diverse ethnic traditions, which is critical for cultivating holistic tolerance.